Preparation method of conductive oxidation film on surface of magnesium-lithium alloy

By preparing the Ni matrix conductive oxide film on the surface of magnesium lithium alloy, and using a multi-step chemical treatment process, the problem of difficult to take into account both the corrosion resistance and the conductivity of the surface oxide film on the magnesium lithium alloy is solved, and a uniform and tight conductive oxide film layer is achieved, with excellent conductivity and corrosion resistance.

CN119876921APending Publication Date: 2025-04-25HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510093279.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The oxide film spontaneously formed on the surface of magnesium lithium alloy is loose and porous, resulting in poor corrosion resistance, and the conductivity and corrosion resistance are in conflicting relationships, making it difficult to improve corrosion resistance while ensuring conductivity.

Method used

By preparing a conductive oxide film with Ni as the matrix on the surface of the magnesium lithium alloy, a multi-step chemical treatment process is adopted, including grinding, oil removal, descaling, activation, removal of the oxide film and metal plating treatment, forming a uniform and tight conductive oxide film layer.

Benefits of technology

The prepared conductive oxide film layer has good conductivity and corrosion resistance, with a surface resistance of 5.45mΩ and a corrosion resistance titration result of 53s, which solves the problem that it is difficult to take into account both the corrosion resistance and the conductivity of the surface oxide film of magnesium lithium alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876921A_ABST
    Figure CN119876921A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a magnesium-lithium alloy surface conductive oxidation film, and belongs to the technical field of surface treatment. The invention aims to solve the problems that an existing magnesium-lithium alloy oxidation film layer is poor in corrosion resistance and conductivity, and a surface oxidation film cannot give consideration to corrosion resistance and conductivity at the same time. The method comprises the steps of 1, polishing; 2, removing oil; 3, descaling; 4, primary activation; 5, removing an oxidation film; 6, secondary activation; 7, pre-filming treatment; 8, pre-plating treatment; and 9, metal coating treatment. The conductive oxidation film layer with excellent conductivity and corrosion resistance is prepared on the surface of the magnesium-lithium alloy part; a conductive oxide film on the surface of the magnesium-lithium alloy prepared by the method is uniformly distributed, is tightly combined and has no phenomena of cracks, defects and the like; the conductivity and corrosion resistance are both considered, the average value of the surface resistance is 5.45 m omega, and the average value of a corrosion resistance titration result is 53s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment, and in particular relates to a method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy. Background Art

[0002] At present, the materials in the fields of aerospace and military industry require lightweight equipment while ensuring the stability of the equipment. In these application fields, not only higher requirements are placed on the comprehensive performance of materials, but also the lightweight of materials is hoped to increase the Mach number and increase the flight distance, which poses a severe challenge to the density of structural materials. It is understood that the most commonly used lightweight alloys in the above fields include aluminum alloys, traditional magnesium alloys, etc. Among them, the application history of magnesium alloys is much shorter than that of aluminum alloys, but with its lightweight and recyclable characteristics, it has become a rapidly emerging engineering material in modern industry. Among them, the density is less than 1.5g / cm 3 The development and application of magnesium-lithium alloys with higher specific strength fills the gap between traditional magnesium alloys and polymer non-metallic materials. Magnesium-lithium alloys have attracted attention in special fields at home and abroad due to their unique advantages, and a large amount of resources have been given to support their development and application.

[0003] However, the oxide film spontaneously formed on the surface of magnesium-lithium alloy is loose and porous, and the second phase or other impurity elements inside the alloy will cause micro-galvanic corrosion. Therefore, the corrosion resistance of magnesium-lithium alloy is poor, which seriously affects its large-scale engineering application; and for some magnesium-lithium alloy parts used in special environments / fields, in addition to certain requirements for their corrosion resistance, there are also certain requirements for their surface conductivity. However, the corrosion resistance and conductivity of the conductive oxide film are contradictory. Since the oxide film has corrosion resistance and insulation, the better the corrosion resistance of the film, the worse its conductivity. Therefore, the key to the conductive oxidation process of magnesium-lithium alloy parts lies in how to find the best balance between the two, so that the obtained film has both good corrosion resistance and good conductivity to ensure electrical continuity. Summary of the invention

[0004] The purpose of the present invention is to solve the problems that the existing magnesium-lithium alloy oxide film has poor corrosion resistance and conductivity, and the surface oxide film cannot take into account both corrosion resistance and conductivity, and to provide a method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy.

[0005] A method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy is specifically completed by the following steps:

[0006] 1. Polishing:

[0007] First, the burrs on the surface of the magnesium-lithium alloy are cleaned, and then the magnesium-lithium alloy is polished with sandpaper, cleaned, and dried to obtain the polished magnesium-lithium alloy;

[0008] 2. Oil removal:

[0009] First, remove the grease and dirt on the surface of the polished magnesium-lithium alloy by wiping or brushing; then wash with water, then put it into a chemical degreasing agent for pre-degreasing at room temperature for a period of time, heat it for degreasing for a period of time, wash with water, then put it into a neutralization treatment agent for treatment at room temperature for a period of time, and finally wash it with water to obtain the degreased magnesium-lithium alloy;

[0010] 3. Descaling:

[0011] The degreased magnesium-lithium alloy is immersed in a descaling agent for a period of time, and then washed with water to obtain a descaled magnesium-lithium alloy;

[0012] 4. One-time activation:

[0013] The descaled magnesium-lithium alloy is immersed in a pickling solution for a period of time, and then washed with water to obtain a primary activated magnesium-lithium alloy;

[0014] 5. Remove the oxide film:

[0015] The magnesium-lithium alloy after the primary activation is immersed in a magnesium-lithium alloy deoxidizing agent at a temperature of 70° C. to 90° C. for a period of time to remove the oxide film on the surface of the magnesium-lithium alloy, and then washed with water to obtain the magnesium-lithium alloy after the oxide film is removed;

[0016] 6. Secondary activation:

[0017] The magnesium-lithium alloy after the oxide film is removed is immersed in a pickling solution for a period of time, and then washed with water to obtain a magnesium-lithium alloy after secondary activation;

[0018] 7. Pre-film treatment:

[0019] The magnesium-lithium alloy after secondary activation is immersed in a magnesium alloy pre-filming treatment solution at a temperature of 25° C. to 45° C. for a period of time, and then washed with water to obtain a magnesium-lithium alloy after pre-filming treatment;

[0020] 8. Pre-plating treatment:

[0021] The pre-plated magnesium-lithium alloy is immersed in a magnesium alloy pre-plating treatment solution at a temperature of 70° C. to 95° C. for a period of time, and then washed with water to obtain the pre-plated magnesium-lithium alloy;

[0022] 9. Metal plating treatment:

[0023] The pre-plated magnesium-lithium alloy is immersed in a metal plating solution at a temperature of 40°C to 45°C for a period of time, and then washed, dried, and baked to obtain a magnesium-lithium alloy with a conductive oxide film on the surface;

[0024] The metal plating solution described in step nine contains 25 g / L to 30 g / L nickel sulfate, 25 / L to 32 g / L sodium hypophosphite, 15 g / L to 21 g / L anhydrous sodium acetate, 12 mL / L to 15 mL / L lactic acid, 0.05 g / L to 0.06 g / L citric acid, 0.2 g / L to 0.5 g / L propionic acid, 0.03 g / L to 0.04 g / L succinic acid, 0.4 mg / L to 0.8 g / L copper sulfate, and the solvent is water.

[0025] Principle of the present invention:

[0026] The invention plates a conductive oxide film with Ni as the matrix on the surface of the magnesium-lithium alloy through chemical reaction.

[0027] Advantages of the present invention:

[0028] 1. The present invention prepares a conductive oxide film layer with excellent conductivity and corrosion resistance on the surface of magnesium-lithium alloy parts;

[0029] 2. The conductive oxide film on the surface of the magnesium-lithium alloy prepared by the present invention is evenly distributed, tightly bonded, and free of cracks and defects; and it takes both conductivity and corrosion resistance into consideration, with an average surface resistance of 5.45 mΩ and an average corrosion resistance titration result of 53s. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a physical picture of the magnesium-lithium alloy with a conductive oxide film on the surface prepared in Example 1;

[0031] Figure 2 This is an electronic scanning image of the cross section of the surface coating of the magnesium-lithium alloy with a conductive oxide film prepared in Example 1;

[0032] Figure 3 The energy dispersive X-ray spectrometer analysis diagram of the magnesium-lithium alloy with a conductive oxide film on the surface prepared in Example 1, wherein (a) is an element distribution diagram of the cross section of Example 1, (b) is a Mg element distribution diagram of the cross section of Example 1, (c) is a Ni element distribution diagram of the cross section of Example 1, and (d) is a Al element distribution diagram of the cross section of Example 1;

[0033] Figure 4 The surface corrosion resistance test report of the magnesium-lithium alloy with a conductive oxide film prepared in Example 1 according to HB5061-77;

[0034] Figure 5 The test report of the surface conductivity of the magnesium-lithium alloy with a conductive oxide film on the surface prepared in Example 1 according to GB / T351-2019;

[0035] Figure 6This is an electronic scanning image of the cross section of the surface coating of the magnesium-lithium alloy with a conductive oxide film prepared in Example 2;

[0036] Figure 7 This is an electron scanning image of the cross section of the surface coating of the magnesium-lithium alloy with a conductive oxide film prepared in Example 3. DETAILED DESCRIPTION

[0037] Specific implementation method 1: This implementation method is a method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy, which is specifically completed by the following steps:

[0038] 1. Polishing:

[0039] First, the burrs on the surface of the magnesium-lithium alloy are cleaned, and then the magnesium-lithium alloy is polished with sandpaper, cleaned, and dried to obtain the polished magnesium-lithium alloy;

[0040] 2. Oil removal:

[0041] First, remove the grease and dirt on the surface of the polished magnesium-lithium alloy by wiping or brushing; then wash with water, then put it into a chemical degreasing agent for pre-degreasing at room temperature for a period of time, heat it for degreasing for a period of time, wash with water, then put it into a neutralization treatment agent for treatment at room temperature for a period of time, and finally wash it with water to obtain the degreased magnesium-lithium alloy;

[0042] 3. Descaling:

[0043] The degreased magnesium-lithium alloy is immersed in a descaling agent for a period of time, and then washed with water to obtain a descaled magnesium-lithium alloy;

[0044] 4. One-time activation:

[0045] The descaled magnesium-lithium alloy is immersed in a pickling solution for a period of time, and then washed with water to obtain a primary activated magnesium-lithium alloy;

[0046] 5. Remove the oxide film:

[0047] The magnesium-lithium alloy after the primary activation is immersed in a magnesium-lithium alloy deoxidizing agent at a temperature of 70° C. to 90° C. for a period of time to remove the oxide film on the surface of the magnesium-lithium alloy, and then washed with water to obtain the magnesium-lithium alloy after the oxide film is removed;

[0048] 6. Secondary activation:

[0049] The magnesium-lithium alloy after the oxide film is removed is immersed in a pickling solution for a period of time, and then washed with water to obtain a magnesium-lithium alloy after secondary activation;

[0050] 7. Pre-film treatment:

[0051] The magnesium-lithium alloy after secondary activation is immersed in a magnesium alloy pre-filming treatment solution at a temperature of 25° C. to 45° C. for a period of time, and then washed with water to obtain a magnesium-lithium alloy after pre-filming treatment;

[0052] 8. Pre-plating treatment:

[0053] The pre-plated magnesium-lithium alloy is immersed in a magnesium alloy pre-plating treatment solution at a temperature of 70° C. to 95° C. for a period of time, and then washed with water to obtain the pre-plated magnesium-lithium alloy;

[0054] 9. Metal plating treatment:

[0055] The pre-plated magnesium-lithium alloy is immersed in a metal plating solution at a temperature of 40°C to 45°C for a period of time, and then washed, dried, and baked to obtain a magnesium-lithium alloy with a conductive oxide film on the surface;

[0056] The metal plating solution described in step nine contains 25 g / L to 30 g / L nickel sulfate, 25 / L to 32 g / L sodium hypophosphite, 15 g / L to 21 g / L anhydrous sodium acetate, 12 mL / L to 15 mL / L lactic acid, 0.05 g / L to 0.06 g / L citric acid, 0.2 g / L to 0.5 g / L propionic acid, 0.03 g / L to 0.04 g / L succinic acid, 0.4 mg / L to 0.8 g / L copper sulfate, and the solvent is water.

[0057] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that in step 1, the burrs on the surface of the magnesium-lithium alloy are firstly removed with a file, and then the surface is polished with 800 mesh, 1200 mesh, and 2000 mesh sandpaper in sequence until the surface is smooth; then the surface is ultrasonically washed for 5min to 10min, and dried to obtain a magnesium-lithium alloy with a smooth surface. The other steps are the same as those in specific implementation method 1.

[0058] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the concentration of NaOH in the chemical degreasing agent described in step two is 80g / L-90g / L, the concentration of Na3PO4·12H2O is 10g / L-15g / L, and the solvent is water; the time for pre-degreasing at room temperature in step two is 5min-10min; the temperature for degreasing at elevated temperature is 35℃-45℃, and the time for degreasing at elevated temperature is 5min-10min; the neutralization treatment reagent described in step two is hydrochloric acid with a mass fraction of 1%-3%; the time for treatment at room temperature in step two in the neutralization treatment reagent is 1min-15min. The other steps are the same as specific implementation method one or two.

[0059] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the descaling agent described in step 3 is purchased from Harbin Sanyong Metal Surface Technology Co., Ltd.; in step 3, the degreased magnesium-lithium alloy is immersed in the descaling agent at a temperature of 30°C to 45°C for 1 min to 10 min. The other steps are the same as specific embodiments 1 to 3.

[0060] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the pickling solution in step 4 is HNO3 with a mass fraction of 10% to 15%; in step 4, the descaled magnesium-lithium alloy is immersed in the pickling solution for 3 to 5 minutes. The other steps are the same as those in specific implementation methods 1 to 4.

[0061] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: in step 5, the magnesium-lithium alloy after the primary activation is immersed in a magnesium-lithium alloy deoxidation film agent at a temperature of 70°C to 90°C for 5min to 12min; the magnesium-lithium alloy deoxidation film agent in step 5 is purchased from Harbin Juzuo Machinery Manufacturing Co., Ltd. The other steps are the same as specific embodiments 1 to 5.

[0062] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the pickling solution in step 6 is HNO3 with a mass fraction of 10% to 15%; in step 6, the magnesium-lithium alloy after the oxide film is removed is immersed in the pickling solution for 3 to 5 minutes. The other steps are the same as those in specific embodiments 1 to 6.

[0063] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: in step 7, the magnesium-lithium alloy after secondary activation is immersed in a magnesium alloy pre-filming treatment solution at a temperature of 25°C to 45°C for 5min to 10min; the magnesium alloy pre-filming treatment solution in step 7 is purchased from Harbin Sanyong Metal Surface Technology Co., Ltd. The other steps are the same as specific embodiments 1 to 7.

[0064] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the magnesium alloy pre-plating treatment solution described in step 8 is purchased from Harbin Sanyong Metal Surface Technology Co., Ltd.; in step 8, the magnesium-lithium alloy after pre-filming treatment is immersed in the magnesium alloy pre-plating treatment solution at a temperature of 70°C to 95°C for 5min to 20min. The other steps are the same as specific embodiments 1 to 8.

[0065] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that in step 9, the magnesium-lithium alloy after pre-plating is immersed in a metal plating liquid at a temperature of 40°C to 45°C for 60min to 90min; the drying temperature in step 9 is 20°C to 30°C, and the drying time is 10min to 15min; the drying temperature in step 9 is 50°C to 60°C, and the drying time is 0.5h to 1h. The other steps are the same as those in specific embodiments 1 to 9.

[0066] The following examples are used to verify the beneficial effects of the present invention:

[0067] Embodiment 1: A method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy is specifically completed by the following steps:

[0068] 1. Polishing:

[0069] First, the burrs on the surface of the magnesium-lithium alloy LAZ931 were removed with a file, and then the surface was polished with 800 mesh, 1200 mesh, and 2000 mesh sandpaper in sequence until the surface was smooth; then the surface was ultrasonically washed for 5 minutes and dried to obtain the polished magnesium-lithium alloy;

[0070] 2. Oil removal:

[0071] First, remove the grease and dirt on the surface of the polished magnesium-lithium alloy by wiping or brushing; then wash with water, then put it into a chemical degreasing agent for pre-degreasing at room temperature for a period of time, heat it for degreasing for a period of time, wash with water, then put it into a neutralization treatment agent for treatment at room temperature for a period of time, and finally wash it with water to obtain the degreased magnesium-lithium alloy;

[0072] The concentration of NaOH in the chemical degreasing agent described in step 2 is 80 g / L, the concentration of Na3PO4·12H2O is 15 g / L, and the solvent is water;

[0073] In step 2, the pre-degreasing time at room temperature is 5 minutes, the temperature of the degreasing at elevated temperature is 35°C, and the degreasing time at elevated temperature is 10 minutes;

[0074] The neutralization reagent in step 2 is 2% hydrochloric acid by mass;

[0075] In step 2, the treatment time in the neutralization treatment reagent at room temperature is 15 minutes;

[0076] 3. Descaling:

[0077] The degreased magnesium-lithium alloy is immersed in a descaling agent for a period of time, and then washed with water to obtain a descaled magnesium-lithium alloy;

[0078] The descaling agent described in step 3 was purchased from Harbin Sanyong Metal Surface Technology Co., Ltd.

[0079] In step 3, the degreased magnesium-lithium alloy is immersed in a descaling agent at a temperature of 45° C. for 10 minutes;

[0080] 4. One-time activation:

[0081] The descaled magnesium-lithium alloy is immersed in a pickling solution for a period of time, and then washed with water to obtain a primary activated magnesium-lithium alloy;

[0082] The pickling solution described in step 4 is HNO3 with a mass fraction of 15%;

[0083] In step 4, the descaled magnesium-lithium alloy is immersed in the pickling solution for 3 minutes;

[0084] 5. Remove the oxide film:

[0085] The magnesium-lithium alloy after the primary activation is immersed in a magnesium-lithium alloy deoxidizing agent at a temperature of 90° C. for a period of time to remove the oxide film on the surface of the magnesium-lithium alloy, and then washed with water to obtain the magnesium-lithium alloy after the oxide film is removed;

[0086] In step 5, the activated magnesium-lithium alloy is immersed in a magnesium-lithium alloy deoxidizing agent at a temperature of 90° C. for 2 minutes;

[0087] The magnesium-lithium alloy deoxidation film agent described in step 5 was purchased from Harbin Juzuo Machinery Manufacturing Co., Ltd.;

[0088] 6. Secondary activation:

[0089] The magnesium-lithium alloy after the oxide film is removed is immersed in a pickling solution for a period of time, and then washed with water to obtain a magnesium-lithium alloy after secondary activation;

[0090] The pickling solution described in step 6 is HNO3 with a mass fraction of 15%;

[0091] In step 6, the magnesium-lithium alloy after the oxide film is removed is immersed in a pickling solution for 5 minutes;

[0092] 7. Pre-film treatment:

[0093] The magnesium-lithium alloy after secondary activation is immersed in a magnesium alloy pre-filming treatment solution at a temperature of 45° C. for a period of time, and then washed with water to obtain a magnesium-lithium alloy after pre-filming treatment;

[0094] In step 7, the magnesium-lithium alloy after secondary activation is immersed in a magnesium alloy pre-film treatment solution at a temperature of 45° C. for 10 minutes;

[0095] The magnesium alloy pre-film treatment solution described in step 7 was purchased from Harbin Sanyong Metal Surface Technology Co., Ltd.

[0096] 8. Pre-plating treatment:

[0097] Immersing the pre-plated magnesium-lithium alloy in a magnesium alloy pre-plating treatment solution at a temperature of 95° C. for a period of time, and then washing with water to obtain a pre-plated magnesium-lithium alloy;

[0098] The magnesium alloy pre-plating treatment solution described in step eight is purchased from Harbin Sanyong Metal Surface Technology Co., Ltd.;

[0099] In step eight, the magnesium-lithium alloy after the pre-filming treatment is immersed in a magnesium alloy pre-plating treatment solution at a temperature of 95° C. for 10 minutes;

[0100] 9. Metal plating treatment:

[0101] The pre-plated magnesium-lithium alloy is immersed in a metal plating solution at a temperature of 40° C. for 60 minutes, then washed with water, dried, and baked to obtain a magnesium-lithium alloy with a conductive oxide film on the surface;

[0102] The metal plating solution in step nine comprises 25 g / L nickel sulfate, 30 g / L sodium hypophosphite, 15 g / L anhydrous sodium acetate, 12 mL / L lactic acid, 0.05 g / L citric acid, 0.2 g / L propionic acid, 0.03 g / L succinic acid, 0.4 mg / L copper sulfate, and water as the solvent;

[0103] The drying temperature in step nine is 20°C and the drying time is 15 minutes;

[0104] The drying temperature in step nine is 60° C. and the drying time is 1 hour.

[0105] Figure 1 This is a physical picture of the magnesium-lithium alloy with a conductive oxide film on the surface prepared in Example 1;

[0106] from Figure 1 It can be seen that the conductive oxide film on the surface of the magnesium-lithium alloy prepared in Example 1 is uniform and compact, without cracks and defects.

[0107] The cross section of the conductive oxide film on the surface of the magnesium-lithium alloy with a conductive oxide film prepared in Example 1 was analyzed by electron scanning and energy dispersive X-ray spectrometry. The analysis results are as follows: Figure 2 , Figure 3 .

[0108] Figure 2 This is an electronic scanning image of the cross section of the surface coating of the magnesium-lithium alloy with a conductive oxide film prepared in Example 1;

[0109] Figure 3 The energy dispersive X-ray spectrometer analysis diagram of the magnesium-lithium alloy with a conductive oxide film on the surface prepared in Example 1, wherein (a) is an element distribution diagram of the cross section of Example 1, (b) is a Mg element distribution diagram of the cross section of Example 1, (c) is a Ni element distribution diagram of the cross section of Example 1, and (d) is a Al element distribution diagram of the cross section of Example 1;

[0110] Depend on Figure 2 and Figure 3 It can be seen that the conductive oxide film on the surface of the magnesium-lithium alloy is relatively evenly distributed on the surface of the magnesium-lithium alloy, is tightly combined, and has no cracks or defects.

[0111] The cross section of the conductive oxide film on the surface of the magnesium-lithium alloy with a conductive oxide film prepared in Example 1 was subjected to a surface corrosion resistance test according to HB5061-77 and a surface conductivity test according to GB / T351-2019. The test results are as follows: Figure 4 , Figure 5 .

[0112] Figure 4 The surface corrosion resistance test report of the magnesium-lithium alloy with a conductive oxide film prepared in Example 1 according to HB5061-77;

[0113] Figure 5 The test report of the surface conductivity of the magnesium-lithium alloy with a conductive oxide film on the surface prepared in Example 1 according to GB / T351-2019;

[0114] from Figure 4 and Figure 5 It can be seen that: a mixed solution of 0.05g potassium permanganate, 5mL of 95% nitric acid, and 95mL of distilled water was used for surface corrosion resistance titration, and the titration results were 56s, 50s, and 53s, with an average value of 53s; a DC low resistance tester was used to test the surface conductivity of the conductive oxide film on the surface of the magnesium-lithium alloy, and its resistance was 5.32mΩ, 5.47mΩ, and 5.56mΩ, with an average value of 5.45mΩ.

[0115] Example 2: The difference between this example and Example 1 is that the metal plating solution in step 9 contains 25 g / L nickel sulfate, 30 g / L sodium hypophosphite, 15 g / L anhydrous sodium acetate, 12 mL / L lactic acid, and water as the solvent. The other steps and parameters are the same as those in Example 1.

[0116] Figure 6 This is an electronic scanning image of the cross section of the surface coating of the magnesium-lithium alloy with a conductive oxide film prepared in Example 2;

[0117] from Figure 6 It can be seen that the conductive oxide film on the surface of the magnesium-lithium alloy prepared in Example 2 is uneven and has defects such as stripes and protrusions.

[0118] The cross-section of the conductive oxide film on the surface of the magnesium-lithium alloy with a conductive oxide film prepared in Example 2 was subjected to surface corrosion resistance testing according to HB5061-77 and to surface corrosion resistance testing according to GB / T351-2019, and the average values ​​of the test results were 35s and 12.45mΩ, respectively.

[0119] Example 3: The difference between this example and Example 1 is that the metal plating solution in step 9 contains 25 g / L nickel sulfate, 30 g / L sodium hypophosphite, 15 g / L anhydrous sodium acetate, 12 mL / L lactic acid, 0.2 g / L propionic acid, 0.03 g / L succinic acid, and water as the solvent. The other steps and parameters are the same as those in Example 1.

[0120] Figure 7This is an electronic scanning image of the cross section of the surface coating of the magnesium-lithium alloy with a conductive oxide film prepared in Example 3;

[0121] from Figure 7 It can be seen that the conductive oxide film on the surface of the magnesium-lithium alloy prepared in Example 3 is uneven, has small protrusions, and is slightly thinner than the conductive oxide film in Example 1.

[0122] The cross-section of the conductive oxide film on the surface of the magnesium-lithium alloy with a conductive oxide film prepared in Example 3 was subjected to surface corrosion resistance testing according to HB5061-77 and to surface corrosion resistance testing according to GB / T351-2019, and the average values ​​of the test results were 42s and 8.91mΩ, respectively.

Claims

1. A method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy, characterized in that The preparation method is specifically completed according to the following steps:

1. Polishing: First, the burrs on the surface of the magnesium-lithium alloy are cleaned, and then the magnesium-lithium alloy is polished with sandpaper, cleaned, and dried to obtain the polished magnesium-lithium alloy; 2. Oil removal: First, remove the grease and dirt on the surface of the polished magnesium-lithium alloy by wiping or brushing; then wash with water, then put it into a chemical degreasing agent for pre-degreasing at room temperature for a period of time, heat it for degreasing for a period of time, wash with water, then put it into a neutralization treatment agent for treatment at room temperature for a period of time, and finally wash it with water to obtain the degreased magnesium-lithium alloy; 3. Descaling: The degreased magnesium-lithium alloy is immersed in a descaling agent for a period of time, and then washed with water to obtain a descaled magnesium-lithium alloy; 4. One-time activation: The descaled magnesium-lithium alloy is immersed in a pickling solution for a period of time, and then washed with water to obtain a primary activated magnesium-lithium alloy; 5. Remove the oxide film: The magnesium-lithium alloy after the primary activation is immersed in a magnesium-lithium alloy deoxidizing agent at a temperature of 70° C. to 90° C. for a period of time to remove the oxide film on the surface of the magnesium-lithium alloy, and then washed with water to obtain the magnesium-lithium alloy after the oxide film is removed; 6. Secondary activation: The magnesium-lithium alloy after the oxide film is removed is immersed in a pickling solution for a period of time, and then washed with water to obtain a magnesium-lithium alloy after secondary activation; 7. Pre-film treatment: The magnesium-lithium alloy after secondary activation is immersed in a magnesium alloy pre-filming treatment solution at a temperature of 25° C. to 45° C. for a period of time, and then washed with water to obtain a magnesium-lithium alloy after pre-filming treatment; 8. Immersing the pre-plated magnesium-lithium alloy in a magnesium alloy pre-plating treatment solution at a temperature of 70° C. to 95° C. for a period of time, and then washing with water to obtain the pre-plated magnesium-lithium alloy; 9. Metal plating treatment: The pre-plated magnesium-lithium alloy is immersed in a metal plating solution at a temperature of 40°C to 45°C for a period of time, and then washed, dried, and baked to obtain a magnesium-lithium alloy with a conductive oxide film on the surface; The metal plating solution described in step nine contains 25 g / L to 30 g / L nickel sulfate, 25 / L to 32 g / L sodium hypophosphite, 15 g / L to 21 g / L anhydrous sodium acetate, 12 mL / L to 15 mL / L lactic acid, 0.05 g / L to 0.06 g / L citric acid, 0.2 g / L to 0.5 g / L propionic acid, 0.03 g / L to 0.04 g / L succinic acid, 0.4 mg / L to 0.8 g / L copper sulfate, and the solvent is water.

2. The method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy according to claim 1, characterized in that In step 1, the burrs on the surface of the magnesium-lithium alloy are first removed with a file, and then polished with 800-mesh, 1200-mesh, and 2000-mesh sandpapers in sequence until the surface is smooth; then ultrasonically washed for 5 min to 10 min, and dried to obtain a magnesium-lithium alloy with a smooth surface.

3. The method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy according to claim 1, characterized in that The concentration of NaOH in the chemical degreasing agent described in step 2 is 80g / L-90g / L, the concentration of Na3PO4·12H2O is 10g / L-15g / L, and the solvent is water; the time for pre-degreasing at room temperature in step 2 is 5min-10min; the temperature for degreasing at elevated temperature is 35°C-45°C, and the time for degreasing at elevated temperature is 5min-10min; the neutralization treatment reagent described in step 2 is hydrochloric acid with a mass fraction of 1%-3%; the time for treatment at room temperature in step 2 in the neutralization treatment reagent is 1min-15min.

4. The method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy according to claim 1, characterized in that In step three, the degreased magnesium-lithium alloy is immersed in a descaling agent at a temperature of 30° C. to 45° C. for 1 min to 10 min.

5. The method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy according to claim 1, characterized in that The pickling solution described in step 4 is HNO3 with a mass fraction of 10% to 15%; in step 4, the descaled magnesium-lithium alloy is immersed in the pickling solution for 3 minutes to 5 minutes.

6. The method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy according to claim 1, characterized in that In step 5, the magnesium-lithium alloy after the primary activation is immersed in a magnesium-lithium alloy deoxidizing film agent at a temperature of 70° C. to 90° C. for 5 min to 12 min.

7. The method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy according to claim 1, characterized in that The pickling solution described in step six is ​​HNO3 with a mass fraction of 10% to 15%; in step six, the magnesium-lithium alloy after the oxide film is removed is immersed in the pickling solution for 3 minutes to 5 minutes.

8. The method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy according to claim 1, characterized in that In step seven, the magnesium-lithium alloy after secondary activation is immersed in a magnesium alloy pre-film treatment solution at a temperature of 25° C. to 45° C. for 5 min to 10 min.

9. The method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy according to claim 1, characterized in that In step eight, the magnesium-lithium alloy after the pre-filming treatment is immersed in a magnesium alloy pre-plating treatment solution at a temperature of 70° C. to 95° C. for 5 min to 20 min.

10. The method for preparing a conductive oxide film on the surface of a magnesium-lithium alloy according to claim 1, characterized in that In step nine, the pre-plated magnesium-lithium alloy is immersed in a metal plating solution at a temperature of 40°C to 45°C for 60min to 90min; the drying temperature in step nine is 20°C to 30°C, and the drying time is 10min to 15min; the drying temperature in step nine is 50°C to 60°C, and the drying time is 0.5h to 1h.

Citation Information

Patent Citations

  • Multi-layer chemical nickel plating processing method of magnesium-lithium alloys

    CN105483658A

  • Magnesium-lithium alloy ionic liquid chemical conversion solution and method for forming conductive oxidation film

    CN107740078A

  • Chemical nickel-plating method on magnesium alloy surface

    CN1500910A

  • Plating Process of Nickel on Magnesium Alloy

    KR1020050014186A